Effects of histone acetyltransferase and deacetylase inhibitors on the expression of S100A genes after TLR4 and TLR2 stimulation in human dental pulp cells - Holger Jungbluth; Dominik Kraus; Diana Lalaouni; Sarah Hossam Fahmy; Jochen Winter; Søren Jepsen (Heliyon)
Objectives: Histone acetylation has been suggested as a promising target for pharmacological intervention in regenerative endodontic (RET) and vital pulp therapy (VPT). S100 proteins are closely linked to processes affected by inhibitors of histone acetylation (HATi) and deacetylation (HDACi) (e.g. differentiation and mineralization). The present study analyzed whether HATi or HDACi modulate the expression of S100A genes in human dental pulp cells (hDPCs) in the presence/absence of TLR4/2 agonists. Materials and Methods: hDPCs were stimulated with HDAC inhibitors Trichostatin (TSA), Valproic acid (VPA), or HAT inhibitor MG149 alone or in presence of LPS (TLR4 agonist) or PAM3CSK4 (TLR2 agonist) for 4 and 24h, respectively. Expression of 13 S100A genes (S100A1/-A2/-A3/-A4/-A6/-A7/-A8/-A9/-A10/-A11/-A13/-A14/-A16) was analyzed using qPCR. Extra- and intracellular S100A4, -A7, and -A10 proteins were quantified by ELISA. After dose-dependent metabolic activity testing, hDPCs were stimulated with 0.1 ng/ml S100A10 (4/24h) and expression of the 13 S100A genes and markers associated with inflammation and/or differentiation/proliferation were analyzed (IL-10; HMGB-1; RAGE; TLR2/4; NGF; VEGF; FGF-1/-2; BMP-2; NANOG; OCT3/4; ALP; COL1A1). Analysis of variance (ANOVA) followed by tukey post-hoc-test was calculated. Results: HDAC and HAT inhibitors significantly altered the expression of S100A genes in hDPCs both in presence and absence of LPS and Pam3CSK4, respectively. Pam3CSK4 and MG149 induced the strongest elevation of S100A gene expression. A stimulation with S100A10 protein led to increased S100A13 and TLR2, and decreased NANOG and RAGE gene expression. Conclusions: The promising effects of HATi and HDACi in RET and VPT appear to be at least partly related to their impact on S100A gene expression. Clinical Relevance: S100A proteins have previously been shown to be involved in crucial processes during RET and VPT [1–3]. The present study further elucidates the mechanism of action of HATi and HDACi, which are regarded as possible pharmacological additives in RET and VPT.